Cleavage and Sub-Cellular Redistribution of Nuclear Pore Protein 98 by Coxsackievirus B3 Protease 2A Impairs Cardioprotection - Hanson, Paul J.; Hossain, Al Rohet; Qiu, Ye; Zhang, Huifang M.; Zhao, Guangze; Li, Cheng; Lin, Veena; Sulaimon, Saheedat; Vlok, Marli; Fung, Gabriel; Chen, Victoria H.; Jan, Eric; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Myocarditis, inflammation of the heart muscle, affects all demographics and is a major cause of sudden and unexpected death in young people. It is most commonly caused by viral infections of the heart, with coxsackievirus B3 (CVB3) being among the most prevalent pathogens. To understand the molecular pathogenesis of CVB3 infection and provide strategies for developing treatments, we examined the role of a key nuclear pore protein 98 (NUP98) in the setting of viral myocarditis. NUP98 was cleaved as early as 2 h post-CVB3 infection. This cleavage was further verified through both the ectopic expression of viral proteases and in vitro using purified recombinant CVB3 proteases (2A and 3C), which demonstrated that CVB3 2A but not 3C is responsible for this cleavage. By immunostaining and confocal imaging, we observed that cleavage resulted in the redistribution of NUP98 to punctate structures in the cytoplasm. Targeted siRNA knockdown of NUP98 during infection further increased viral protein expression and viral titer, and reduced cell viability, suggesting a potential antiviral role of NUP98. Moreover, we discovered that expression levels of neuregulin-1 (NRG1), a cardioprotective gene, and presenilin-1 (PSEN1), a cellular protease processing the tyrosine kinase receptor ERBB4 of NRG1, were reliant upon NUP98 and were downregulated during CVB3 infection. In addition, expression of these NUP98 target genes in myocardium tissue not only occurred at an earlier phase of infection, but also appeared in areas away from the initial inflammatory regions. Collectively, CVB3-induced cleavage of NUP98 and subsequent impairment of the cardioprotective NRG1-ERBB4/PSEN1 signaling cascade may contribute to increased myocardial damage in the context of CVB3-induced myocarditis. To our knowledge, this is the first study to demonstrate the link between NUP98 and the NRG1 signaling pathway in viral myocarditis.